Terrorist rehabilitation and counter-radicalisation new approaches to counter-terrorism - Gunaratna, Rohan; Jerard, Jolene; Rubin, Lawrence (Cass series on political violence, 2011)
This book seeks to explore the new frontiers in counter-terrorism research, analyses and practice, focusing on the imperative to rehabilitate terrorists.